Development of a Hydrogel Column for Water Removal from Fuels - Henrique L. Goncalves; Patricia B.L. Fregolente; Gabriela M. de Andrade; Maria Regina Wolf Maciel; Leonardo V. Fregolente (Chemical Engineering Transactions, 2021)
The maximum water content in biodiesel is an important specification of quality, since the presence of free water (when the water concentration exceeds the saturation value) leads to microbiological development, degrading the fuel and generating sludge. Also, if a biodiesel with inappropriate water content is employed, problems such as corrosion and performance impairment can happen. Some sources of the water present in biodiesel are the washing process, during the fuel production, and the absorption of water during storage. Therefore, alternative ways to remove water from biodiesel have been studied, leading to new technologies for this purpose. It was demonstrated, in previous works, that dried hydrogels immersed in fuels can remove water even in small concentration. In this study, hydrogels of poly(acrylamide-co-sodium acrylate) were synthesized using different monomers quantities, following a central composite rotational design, aiming the improvement of the swelling characteristics. The highest value of swelling degree was 162, obtained at 20 oC, almost 11 times higher than the value obtained for polyacrylamide hydrogels. Then, based on this formulation, hydrogel discs were employed on a sieve plate column, for the removal of free water from biodiesel on continuous flow. The bed configuration featured on this study was efficient for removing all the free water from the feed being suitable for further applications in water removal from fuels without the bed clogging effect.